2011
DOI: 10.1589/jpts.23.455
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Towel-gathering Exercise and Toe Exercises for the Painful Accessory Navicular

Abstract: Abstract.[Purpose] The towel gathering exercise is commonly chosen in the treatment of painful accessory navicular. However, the effect has not been well documented in clinical settings. So we compared the reduction in pain effect of towel gathering exercise with those of three toe flexor exercises we developed. [Subjects and Methods] Fifteen accessory navicular cases (4 males, 11 females) were chosen as subjects. Their mean age was 20.3±10.7 years old. The three exercises were almost maximal isometric contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, these methods are potentially inconvenient as a result of the setup, portability, and costs in both the clinical and research settings. The towel-gathering exercise is currently prescribed in clinical practice as a strengthening exercise for the toe flexor muscles [ 16 ]. Within the context of this clinical exercise, changes in toe grip strength (TGS) could be assessed as an outcome of strengthening the toe flexor muscles.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are potentially inconvenient as a result of the setup, portability, and costs in both the clinical and research settings. The towel-gathering exercise is currently prescribed in clinical practice as a strengthening exercise for the toe flexor muscles [ 16 ]. Within the context of this clinical exercise, changes in toe grip strength (TGS) could be assessed as an outcome of strengthening the toe flexor muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated the curative effects of raloxifene for the treatment of senile osteoporosis, which resulted in improved patient bone density. Always study, human bones but as sport and adaptability to changes 19 ) . Aerobic exercise, also referred to as green therapy, can achieve results beyond what drug treatment alone can achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the intrinsic muscles of the foot have been reported as an important factor in the MLA 6,7,10,11) . We have also described a lesser-toe exercise (LTE) we have designed [12][13][14] . The toe position for the LTE is the distal interphalangeal joint extension and proximal interphalangeal joint flexion positions, similar to that for the short foot exercise 6,[7][8][9][10]11) .…”
Section: Introductionmentioning
confidence: 99%